A Role of Caveolae in Trabecular Meshwork Mechanosensing and Contractile Tone - De Ieso, Michael L.; Kuhn, Megan; Bernatchez, Pascal; Elliott, Michael H.; Stamer, W. Daniel (Frontiers in Cell and Developmental Biology, 2022)
Polymorphisms in the CAV1/2 gene loci impart increased risk for primary open-angle glaucoma (POAG). CAV1 encodes caveolin-1 (Cav1), which is required for biosynthesis of plasma membrane invaginations called caveolae. Cav1 knockout mice exhibit elevated intraocular pressure (IOP) and decreased outflow facility, but the mechanistic role of Cav1 in IOP homeostasis is unknown. We hypothesized that caveolae sequester/inhibit RhoA, to regulate trabecular meshwork (TM) mechanosensing and contractile tone. Using phosphorylated myosin light chain (pMLC) as a surrogate indicator for Rho/ROCK activity and contractile tone, we found that pMLC was elevated in Cav1-deficient TM cells compared to control (131±10%, n=10, p=0.016). Elevation of pMLC levels following Cav1 knockdown occurred in cells on a soft surface (137±7%, n=24, p<0.0001), but not on a hard surface (122±17%, n=12, p=0.22). In Cav1-deficient TM cells where pMLC was elevated, Rho activity was also increased (123±7%, n=6, p=0.017), suggesting activation of the Rho/ROCK pathway. Cyclic stretch reduced pMLC/MLC levels in TM cells (69±7% n=9, p=0.002) and in Cav1-deficient TM cells, although not significantly (77±11% n=10, p=0.059). Treatment with the Cav1 scaffolding domain mimetic, cavtratin (1μM) caused a reduction in pMLC (70±5% n=7, p=0.001), as did treatment with the scaffolding domain mutant cavnoxin (1μM) (82±7% n=7, p=0.04). Data suggest that caveolae differentially regulate RhoA signaling, and that caveolae participate in TM mechanotransduction. Cav1 regulation of these key TM functions provide evidence for underlying mechanisms linking polymorphisms in the Cav1/2 gene loci with increased POAG risk.